Effect of native and L-arginine-modified raspberry shoot extracts on electrocardiogram parameters of rats and status of the antioxidant system under the conditions of experimental doxorubicin cardiomyopathy in rats - Horopashna, Daryna; Derymedvid, Lyudmyla (Annals of Mechnikov's Institute, 2025)
Introduction. In folk medicine, raspberry (fruits, leaves and shoots) is applied in treatment of influenza, sore throat. But there is no any information about application raspberry as cardio protective medicine. The aim of the work was study of the effect of raspberry shoot extracts on the state of free radical oxidation processes and electrocardiogram (ECG) parameters in rats with experimental doxorubicin cardiomyopathy. Material & methods. The object of the study was extract of shoot raspberry (ERS) and its modified extract with L-arginine ("RubusArg"); antioxidant effect of extracts was determined by catalase, superoxide dismutase, and reduced glutathione assays; cardiomyopathy was induced by doxorubicin model. Results & discussion. The therapeutic and prophylactic administration of the studied extracts, along with the reference drug quercetin, significantly improved animal survival rates. Survival reached 90% with RubusArg, 80% with both ERS and quercetin, and 70% with catechin. RubusArg demonstrated the strongest suppression of free radical oxidation, as evidenced by a significant 2.1-fold reduction in serum 8-isoprostane levels (p≤0.01). Additionally, myocardial homogenate showed a 1.45-fold decrease in TBA-reactive substances compared to the untreated control. The extract also significantly enhanced antioxidant enzyme activity, increasing catalase levels by 1.28-fold in myocardial homogenate and 1.3-fold in blood serum. Superoxide dismutase activity rose by 1.5-fold in myocardial homogenate and 1.68-fold in blood serum, while myocardial glutathione levels significantly increased by 1.35-fold. Conclusion. The conducted study indicates the promising use of the modified L-arginine raspberry shoot extract, which contains ionized forms of (+)-catechin and epicatechin, for the correction of anthracycline-induced myocardial damage. The application of native and modified L-arginine raspberry shoot extracts (RubusArg) contributes to the improvement of the antioxidant-prooxidant index, reduction of FRO intensity, increased activity of SOD, catalase, increased levels of reduced glutathione, improved ECG parameters, and reduced mortality. Key words: doxorubicin, cardiomyopathy, raspberry shoots, catechins, rats, ECG.